Concepções dos Conselheiros Indígenas sobre o Controle Social da Saúde Indígena do DSEI Manaus: saúde indígena em foco - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This thesis aims to investigate the Social Control of DSEI Manaus governmental actions for the implementation of indigenous health, whose subjects were indigenous counselors seen from the perspective of their actions with the DSEI and thus identify how are the relations of Social Control of the Sanitary District. Indigenous Special (DSEI Manaus) and the various phases of the creation process and the possible difficulties for its implementation. It also sought to point out the possibility of finding solutions to the conflicts existing between indigenous peoples and the Brazilian State in this scenario of insertion in the SUS subsystem and to analyze if there is indigenous protagonism as a preponderant element in the construction of this history of struggles around the politics of indigenous health under the Manaus DSEI. The hypothesis of this work is based on the possibility that the actions of CONDISI would give visibility and make it possible to find solutions to the conflicts existing between the indigenous peoples and the Brazilian State led to the need to investigate the perception of the indigenous counselors about these social control mechanisms of the Subsystem. Indigenous Health Care. That is, whether they consider that such mechanisms would be adequate means for reducing the problems that emerge in this context. To validate the relationship between the constructs, we used an exploratory, descriptive and correlational research, whose nature is qualitative. The field research consists in the systematization of speech acts, based on semi-structured interviews, carried out during CONDISI ordinary and extraordinary meetings in Manaus, as well as in the villages covered by the DSEI, from which aspects are defined. characterize the governmental action with the indigenous regarding the national indigenous health policy. The research shows that CONDISI / MAO has considered the present moment a time of struggle for improvement in the quality of services offered by DSEI, recognizing, however, that they lack more appropriation of their roles as advisors. Thus, it is identified that, given the context of a system that acts as an instrument to enhance the actions of a collegiate that, despite being equal, gives indigenous people the possibility of effective participation in the implementation of indigenous health policy, a fact that does not occurs as expected and recognized by the directors themselves. Finally, the research identifies the emergence of discourse acts in opposition to this state that counselors find themselves in an affirmative praxis of behavioral change in relation to the current scenario, corresponding effectively to the desires of effective counselors.
Conceptions of indigenous councils on the social control of dsei Manaus indian health: indian health in focus
Keywords: Controle Social - Manaus (AM); Acesso aos serviços de saúde - Manaus (AM); CIÊNCIAS SOCIAIS APLICADAS; Saúde indígena; Controle Social; DSEI Manaus; CONDISI